2010
DOI: 10.1111/j.1469-7610.2010.02330.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-adoption contact, adoption communicative openness, and satisfaction with contact as predictors of externalizing behavior in adolescence and emerging adulthood

Abstract: Background-This study examined the relation between three variables related to adoptive family relationships (post-adoption contact between adoptive and birth family members, adoption communicative openness, and satisfaction with contact) and adoptee externalizing behavior in adolescence and emerging adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 24 publications
(33 reference statements)
1
57
1
2
Order By: Relevance
“…Brodzinsky (2005) defines communicative openness within the adoptive family as a ‘willingness of individuals to consider the meaning of adoption in their lives, to share that meaning with others, to explore adoption related issues in the context of family life, to acknowledge and support the child’s dual connection to two families, and perhaps to facilitate contact between these two family systems in one form or another.’ Communicative openness has been found to be positively associated with adjustment and self-esteem in adoptees (Brodzinsky, 2006; Grotevant, Rueter, Von Korff, & Gonzalez, 2011; Lanz et al, 1999). For transracial adoptees, communicative openness regarding adoptive status as well as the child’s racial/ethnic and cultural background are all important.…”
Section: Introductionmentioning
confidence: 99%
“…Brodzinsky (2005) defines communicative openness within the adoptive family as a ‘willingness of individuals to consider the meaning of adoption in their lives, to share that meaning with others, to explore adoption related issues in the context of family life, to acknowledge and support the child’s dual connection to two families, and perhaps to facilitate contact between these two family systems in one form or another.’ Communicative openness has been found to be positively associated with adjustment and self-esteem in adoptees (Brodzinsky, 2006; Grotevant, Rueter, Von Korff, & Gonzalez, 2011; Lanz et al, 1999). For transracial adoptees, communicative openness regarding adoptive status as well as the child’s racial/ethnic and cultural background are all important.…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that adoption is relevant to donor conception, it is important to note that the transition to adolescence presents specific challenges for adopted children, particularly in terms of identity formation (Grotevant, Rueter, Von Korff, & Gonzalez, 2011). It has been shown that adopted adolescents need to integrate their experiences of being adopted into meaningful narratives in order to develop a secure sense of identity.…”
Section: Donor Conception Families (Sperm Egg and Embryo Donation)mentioning
confidence: 99%
“…Given their considerable complexity and variation, open adoption relationships in particular are created and sustained through communication. To date, however, the bulk of open adoption research has focused on the structure of open adoption configurations (e.g., Grotevant et al, 2008) as well as the outcomes of birth-parent contact (e.g., Grotevant, Rueter, Von Korff, & Gonzalez, 2011). An increasing number of communication scholars are turning attention to adoption research; however, this research typically focuses on closed adoption (Colaner & Kranstuber, 2010;Kranstuber & Kellas, 2011), adoption reunion (Scharp, 2013;Scharp & Steuber, 2014), international adoption (Docan-Morgan, 2011;Suter, 2008), and foster adoption (Suter, Baxter, Seurer, & Thomas, 2014).…”
Section: Understanding Open Adoptionmentioning
confidence: 99%
“…For example, instead of bearing the sole responsibility for placing the adoptive child, adoption practitioners now share this responsibility with birth parents, which adds another layer of complexity to the open adoption process. With options evolving and new challenges to consider, it is no surprise adoptive parents and birth parents have to engage in a series of trial-and-error negotiations before finding the right relationship mix for everyone in the triad (Grotevant et al, 2011).…”
Section: Importance Of Adoption Practitioners' Standpointmentioning
confidence: 99%